ANALISIS MEDIA SOSIAL TIKTOK DALAM PEMBENTUKAN KARAKTER SOPAN SANTUN KELAS V SDN LANGENHARJO 02 PATI - Ahmad Elwi Yusro; AY Soegeng Ysh; Eka Sari Setianingsih (STKIP Subang, 2023)
The background that drives this research is the low character of students' environmental care and the absence of innovative character education at Kalicari 02 State Elementary School. The solution to this problem is the Development of an Outbound-Based Game Model in Environmental Care Character in Fifth Grade Elementary School Students. The problem formulations in this study are 1) How is the validity and feasibility of developing an Outbound-based Game Model in Environmental Care Characters in Grade V Elementary School Students, 2) How is the effectiveness of the Outbound-based Game Model in Environmental Care Character in Primary School Grade V Students in improving students' environmental care character. The objectives of this study are 1) To determine the validity and feasibility of developing an outbound-based game model in the character of environmental care in grade V elementary school students, 2) To determine the effectiveness of the Outbound-based Game Model in Environmental Care Character in Grade V Elementary School Students in improving students' environmental care character. The type of research used in this study is research and development (Research and Development) with the ADDIE development model (Analyze, Design, Develop, Implementation, Evaluation). The resulting product is an outbound-based game model in the character of environmental care that has been implemented at Kalicari 02 State Elementary School. The Outbound-Based Game Model in Environmental Care Character in Class V Elementary School Students received model validation results of 85% and 95% with